Research Cycles: Adding More Substance to the Spin. Issue 4 (28th December 2016) - Elman, Colin; Burton, Colleen Dougherty
Abstract : In sciences such as biomedicine, researchers and journal editors are well aware that progress in answering difficult questions generally requires movement through a research cycle: Research on a topic or problem progresses from pure description, through correlational analyses and natural experiments, to phased randomized controlled trials (RCTs). In biomedical research all of these research activities are valued and find publication outlets in major journals. In political science, however, a growing emphasis on valid causal inference has led to the suppression of work early in the research cycle. The result of a potentially myopic emphasis on just one aspect of the cycle reduces incentives for discovery of new types of political phenomena, and more careful, efficient, transparent, and ethical research practices. Political science should recognize the significance of the research cycle and develop distinct criteria to evaluate work at each of its stages.